Light and nutrients modulate the temperature‐sensitivity of growth in phytoplankton - Vanessa Weber de Melo; Marc J.‐F. Suter; Anita Narwani (Limnology and Oceanography Letters)
Abstract In aquatic ecosystems facing climate change, higher temperatures often co‐occur with alterations in resource availability. The metabolic theory of ecology uses activation energy to assess the sensitivity of biological processes to temperature, but neglects how resource availability might modify temperature sensitivities. To understand the impacts of resource limitation on temperature sensitivities, we performed experiments manipulating temperature and three key resources (nitrogen, phosphorus, and light) in six species of freshwater phytoplankton. We measured activation energies of population growth rates and how they were modulated by resource limitation. We find that the interaction of temperature and resource limitation is dependent on the resource type. Phosphorus limitation did not modify the temperature sensitivity of growth rates, light limitation reduced the sensitivity of growth rates to temperature in all species, and nitrogen limitation had species‐dependent effects. We explore how stoichiometry and cell physiology may explain the complex responses of phytoplankton to multiple environmental changes.